2005
DOI: 10.1097/01.ju.0000165340.53381.48
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Provider Volume on Outcomes From Urological Cancer Therapy

Abstract: Evidence that high volume hospitals have better outcomes is increasing for urological cancer surgeries. Whether volume affects quality or better clinicians and services attract more patients can be debated. Centralizing health care will have major health policy implications, ie high volume hospitals may be overwhelmed and low volume hospitals may be at a disadvantage. An alternative would be to attempt to improve outcomes at low volume hospitals by identifying drivers of high quality care at high volume hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
7

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 30 publications
1
66
0
7
Order By: Relevance
“…2 2 In terms of urological oncology several recently reviewed studies demonstrated improved outcomes at HVHs for cancer surgery. 5 Volume-outcomes relationships have been least explored for renal cancer surgery, which interestingly demonstrated the greatest regionalization in the current study.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…2 2 In terms of urological oncology several recently reviewed studies demonstrated improved outcomes at HVHs for cancer surgery. 5 Volume-outcomes relationships have been least explored for renal cancer surgery, which interestingly demonstrated the greatest regionalization in the current study.…”
Section: Discussionmentioning
confidence: 80%
“…3,4 Evidence for and against the volume-quality association was recently reviewed. 5 Although the strength and importance of associations between volume and quality remain subject to varying degrees of controversy depending on the procedure, some evidence exists that the migration of care to HVHs and high volume surgeons is already occurring, with some hospitals abandoning high risk procedures altogether. 6,7 We examined data from a large national hospital admissions database to analyze trends during a 15-year period in the concentration of inpatient surgical and nonsurgical care at HVHs for bladder, renal and prostate cancer.…”
mentioning
confidence: 99%
“…Nonetheless, our study does corroborate previous findings documenting the effect of AHC on RP outcomes. [16][17][18][19] Specifically, RP performed at high AHC hospitals were associated with fewer blood transfusions, were less frequently associated with intraoperative or postoperative complications, and less frequently resulted in length of stay beyond the median. Table 4b-d demonstrates the complex link between AHC and insurance status.…”
Section: Resultsmentioning
confidence: 99%
“…Actuarial 5-year overall survival after radical cystectomy, for example, was 39.0% at high-volume hospitals vs. 35.4% at low-volume hospitals, whereas survival following esophagectomy was 33.7% and 17.4% at high-and low-volume hospitals, respectively [22]. In urologic oncology specifically, most of the focus on volume and outcomes to date has been on radical prostatectomy and radical cystectomy, with fewer studies to date on radical nephrectomy and testis cancer management [23]; these will be discussed in further depth in the articles that follow.…”
Section: The Question Of Surgical Volumementioning
confidence: 99%